2012
DOI: 10.1590/s0004-282x2012005000013
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoplasty as a therapeutic option for lumbar disc degeneration related pain: a retrospective study of 396 cases

Abstract: OBJECTIVES: To make a retrospective analysis and evaluate a clinical response to the control of disc degeneration related pain of 396 patients submitted to percutaneous lumbar nucleoplasty; and to make a record of visual analogical scale (VAS) up to a three-year follow-up after the surgical procedure. METHODS: Analysis of VAS score in 396 patients with lumbar disc degeneration related pain, according to anamnesis, clinical examination and magnetic resonance imaging (MRI), without improvement of previous clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In Mexico, intervertebral disc disease is a highly prevalent socio-economic problem. 7 Percutaneous manual nucleotomy has been shown to be useful as a disc decompression technique to treat pain in patients with lumbar disc hernia, however, its use continues to be controversial 13,17 although good results in more than 70% of the cases are reported in the literature. 4,6,14,15,18,19 In our study, the average age of the patients was 37.95 years, which agrees with that reported by Hijikata 14,15 and Stern 20 while in other studies by Amoretti et al 6 and Kallas et al 17 the average ages reported were 52 and 46 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, intervertebral disc disease is a highly prevalent socio-economic problem. 7 Percutaneous manual nucleotomy has been shown to be useful as a disc decompression technique to treat pain in patients with lumbar disc hernia, however, its use continues to be controversial 13,17 although good results in more than 70% of the cases are reported in the literature. 4,6,14,15,18,19 In our study, the average age of the patients was 37.95 years, which agrees with that reported by Hijikata 14,15 and Stern 20 while in other studies by Amoretti et al 6 and Kallas et al 17 the average ages reported were 52 and 46 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…www.painphysicianjournal.com (24,227,1099,1129,(1190)(1191)(1192)(1193). With Coblation technology, radiofrequency energy is applied to a conductive medium, creating the formation a highly focused plasma field to form around the energized electrodes (24,1099,1129,(1190)(1191)(1192)(1193). The plasma field is composed of highly ionized particles (1193).…”
Section: S110mentioning
confidence: 99%
“…Claims have been made over the past few years that nucleoplasty can produce satisfactory results with fewer serious complications. However, these claims continue to be debated (25,105,227,1099,1129,(1190)(1191)(1192)(1193). Gibson and Waddell (629) in the Cochrane Collaboration review presented the results from 40 RCTs and 2 QRCTs of surgical interventions for lumbar disc prolapse including 17 new trials since the first issue of the review.…”
Section: S110mentioning
confidence: 99%
See 2 more Smart Citations